Diálogos entre política/regime de informação e as competencias em informação dos bibliotecários do Sistema de Biblioteca da Universidade Eduardo Mondlane (SIBUEM) ‒ Moçambique - Munguambe, Rosa Manuela Teixeira Pinto (2019)
The development of librarian information skills has shown to be one of the tools that assist in the satisfaction of the real needs of the users in a library information system, governed by information policies directed to the information actions. However, there have been several approaches to information skills, but there is almost no discussion on the information's interdependence with the information policies of the information system of which the information actions to be practiced with information skills are part. In order to establish a dialogue between information policy and information system and information skills, the present research was developed with the overall objective of analyzing the information skills of librarians from Eduardo Mondlane University library - BCE - from an information policy and system. For the discussion, specific objectives that focused firstly on the presentation of the information policies in Mozambique both from the Government, as well as from EMU (Eduardo Mondlane University) and the BCE rules were drawn up; having followed the mapping of the ECB's information system. From the objectives, information actions of the BCE's librarians were identified within the current information system in order to develop the information skills necessary for the exercise of their librarian activities and to identify the skills of the librarians. With these elements a model was proposed for the creation of an information policy for the development of skills in information appropriate to the context of the librarians under study. For the consolidation of the ideas and discussions on the literature that deal with the specific objectives of this research, a descriptive or explanatory (causal) methodology was used, with an integrated research strategy, based on the articulated combination of qualitative and quantitative approaches to better understand the problem of information skills in the Library and to broaden the basis for the conclusions to be drawn from the analysis of the data collected and compared. Not only the need for appropriate information actions managed by information policies, but also research has shown that the information skills of ECB staff is far from being achieved if the information policies for the library information system not followed. Information actions alone cannot be efficiently performed if the artefacts are not part of the main element of the macro regulatory norms that dictate and enforce the set's life form. They have made noticeable the reasons why Library activities face constraints to achieve efficiency in meeting user needs. Therefore, it is fundamental to formulate a legislative instrument that ensures the accomplishment of the information production cycle with the efficiency and effectiveness in the information system taking into account the constant training of the information players in information skills. That is, to ensure the interconnection and dependence of these elements in the production process.